Agro‐ecological zone and farm diversity are factors associated with haemoglobin and anaemia among rural school‐aged children and adolescents in Ghana. Issue 1 (25th July 2018) - Azupogo, Fusta; Aurino, Elisabetta; Gelli, Aulo; Bosompem, Kwabena M.; Ayi, Irene; Osendarp, Saskia J. M.; Brouwer, Inge D.; Folson, Gloria
Abstract: Understanding contextual risk factors for haemoglobin (Hb) status and anaemia of rural school‐aged children (SAC) and adolescents is critical in developing appropriate interventions to prevent anaemia. We analysed secondary data from the baseline of an impact evaluation of the Ghana School Feeding Programme to determine the severity of anaemia and contextual factors associated with anaemia and Hb status among rural SAC (6–9 years; n = 323) and adolescents (10–17 years; n = 319) in Ghana. We used regression models with variable selection based on backward elimination in our analyses. The mean Hb was 113.8 ± 13.1 g/L, and the overall prevalence of anaemia was 52.3%, being 55.1% and 49.5% among SAC and adolescents, respectively. We identified child's age (β = 2.21, P  < 0.001); farm diversity score (β = 0.59, P  = 0.036); and agro‐ecological zone ( P trend <0.001) as the main predictors of Hb of SAC. Household asset index ( P trend = 0.042) and agro‐ecological zone ( P trend <0.001) were predictors of Hb in adolescents. Agro‐ecological zone and age were predictors of anaemia, but the effect of age was only significant for girls and not boys (prevalence odds ratio [POR] = 1.35, 95% CI [1.04, 1.76] vs. POR = 1.14, 95% CI [0.88, 1.46]). SAC in households with maize stock were less likely to be anaemic (POR = 0.55, 95% CI [0.32, 0.97]). Household dietary diversity score (β = 0.59, P  = 0.033) was associated with Hb status for the full sample only. Anaemia is a severe public health problem among SAC and adolescents in rural Ghana irrespective of sex. Farm diversity score, availability of maize stock in the household, household asset index, and agro‐ecological zone were the main predictors of Hb and anaemia among the rural SAC and adolescents.